Perancangan Portable Folding Furniture untuk Interior Apartemen Tipe Studio - Wijaya, Cindy; Kusumarini, Yusita; suprobo, filipus priyo (Intra, 2015)
Nowadays, studio type apartment become a choice of residence for people even though it has limited space. Therefore, the furniture in the apartment should be a saving space one, because it does not make the circulation of the apartment smaller but it fulfills the needs of the occupant for furniture. There are some methods that be used for this design, that are observation about the occupant’s needs of the furniture and analyze it, designing the furniture then analyze it again, after that make the prototype. Based the analysis, there are four types of main furniture that occupant needs, which are chair, table, bedside and storage. At the end, after design and the prototype making, it can be concluded that the saving space furniture such as folding furniture set is a good choice for studio type apartment. Using multi-layered wood as the material for the design, the key of designing folding furniture is in the shape of it, and the system used like the folding system.